2014
DOI: 10.1097/ijg.0b013e318265bc0b
|View full text |Cite
|
Sign up to set email alerts
|

Ahmed Glaucoma Valve Implantation With Tube Insertion Through the Ciliary Sulcus in Pseudophakic/Aphakic Eyes

Abstract: Ciliary sulcus placement of the tube of AGV effectively reduces IOP and medication use in short term. It has the potential to lower corneal complications of anterior chamber tube insertion and avoids the need for pars plana vitrectomy and tube insertion in patients at higher risk of corneal decompensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…This ratio has previously been reported to range between 0.0 and 31.7%. 5,7,13 and the ratios we found (17.6 and 14.3% in the ACA and CS groups, respectively) is comparable to these. Although the ratio of flat anterior chamber was similar between the groups, the incidence of flat anterior chamber requiring Figure 2 Kaplan-Meier survival curves after Ahmed glaucoma valve implantation in the anterior chamber angle and ciliary sulcus.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This ratio has previously been reported to range between 0.0 and 31.7%. 5,7,13 and the ratios we found (17.6 and 14.3% in the ACA and CS groups, respectively) is comparable to these. Although the ratio of flat anterior chamber was similar between the groups, the incidence of flat anterior chamber requiring Figure 2 Kaplan-Meier survival curves after Ahmed glaucoma valve implantation in the anterior chamber angle and ciliary sulcus.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that CS insertion of tube shunts is a safe and effective alternative to ACA or pars plana insertion. 7,12,13,16 Implantation into the CS in pseudophakic or aphakic patients could prevent the complications associated with ACA placement such as corneal decompensation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study of AGV tube implantation in the ciliary sulcus, Bayer et al (10) found a ratio of hyphema of 14.3%. The greater vascularization of the ciliary sulcus compared with the anterior chamber angle or pars plana may have contributed to these findings (13).…”
Section: Discussionmentioning
confidence: 98%
“…Tube implantation into the pars plana or ciliary sulcus has been investigated as a possible means of reducing contact in cases with a risk of corneal decompensation or peripheral anterior synechiae (PAS) (4,(10)(11)(12). AGV insertion into the ciliary sulcus has been proposed as a more advantageous option because AGV insertion into the pars plana is thought to be associated with more posterior segment complications and more additional inflammation following vitrectomy (13).…”
Section: Introductionmentioning
confidence: 99%